Development of Bifocal Modeling Practicum to Harmonic Vibrations as Innovation in Physics Learning - Sujito, Sujito; Pramono , Nugroho Adi; Sulur, Sulur; Wisodo , Hari; Kurniawan, Bakhrul Rizky (Universitas Negeri Surabaya, 2024)
The era of Industry 5.0 requires physics education to adapt to technological advancements. Students often struggle to understand abstract concepts due to the limitations of tools and methods of learning that are less interactive. This research aims to develop a prototype for a harmonic vibration practical that integrates the Internet of Things (IoT), Augmented Reality (AR), and Virtual Reality (VR) into a single Bifocal Modelling device. This approach allows students to see the application of physics concepts in real-time, enriching their learning experience. The method used is Research and Development (R&D), which consists of Analysis, Design, Development, Implementation, Evaluation (ADDIE). The research results indicate that the use of this technology can enhance student engagement and help them understand the differences between the ideal model and real phenomena. Thus, students not only learn theory but also experience firsthand that makes learning more engaging. In addition, the integration of this technology equips students with the 21st-century skills needed in an increasingly complex job market. This research is expected to provide solutions to the challenges in physics teaching and pave the way for further research related to the application of technology. In this way, the integration of technology in physics education can prepare students to face the complexities of the modern workforce.